SAT0105 Trial of Atorvastatin for the Primary Prevention of Cardiovascular Events in Patients with Rheumatoid Arthritis (TRACE RA). (9th June 2015) - Kitas, G.D.; Nightingale, P.; Armitage, J.; Sattar, N.; TRACE RA Consortium,; Belch, J.; Symmons, D.
Abstract : Background: Rheumatoid arthritis (RA) patients have increased cardiovascular disease (CVD) risk compared to the general population, due to classical and novel risk factors. It is unclear whether primary prevention strategies for CVD are effective in high grade inflammatory conditions such as RA. Objectives: TRACE RA was designed to address the hypothesis that atorvastatin 40mg daily is superior to placebo for the primary prevention of CVD events in RA (ISRCTN: 41829447). Methods: Prospective, randomised, double-blind, placebo-controlled, multicentre trial in RA patients aged >50 years or RA duration >10 years; without known atherosclerotic disease, diabetes, myopathy; not taking statins . All patients were given lifestyle advice. Primary endpoint was a composite of CVD death, non-fatal myocardial infarction, cerebrovascular accident (excluding haemorrhagic stroke), transient ischaemic attack, hospitalised angina, coronary and non-coronary revascularisation. Secondary endpoints included safety outcomes and lipid changes. The trial was designed to have 80% power at p<0.05 to detect a 32% risk reduction with atorvastatin based on 1.8% event rate, using intention to treat analysis over 5 years. Cox regression stratified by centre, Fisher's exact test and the Mann-Whitney test were used for analysis. Results: Trial duration was August 2007 to December 2012. 2986 patients from 102 centres were randomised and followed up for a median of 2.53 years (IQR 1.94-3.50), providing 7, 908 patient-years of follow-up. Atorvastatin and placebo groups were well-matched for age, sex, ethnicity, weight, BMI, RA duration, activity, severity and seropositivity, blood pressure, lipid and glucose levels, diabetes, family history of CVD or diabetes. Current smoking was higher in the atorvastatin group (18.4% v 14.5%, p=0.019). Reduction in LDL-c levels was significantly greater in the atorvastatin group (1.07 mmol/l) compared to placebo (0.14 mmol/l), p<0.001 and reflected reported adherence. In the atorvastatin group 24 patients had a CVD event, compared to 36 in the placebo (hazard ratio 0.66, 95% confidence interval 0.40-1.11, p=0.119). Overall event rate was however lower (0.76%) than anticipated (1.80%) leading to early termination of the trial. Any reported adverse events were similar: 294 (19.7%) in the atorvastatin and 292 (19.5%) in the placebo group, p=0.927. Conclusions: Atorvastatin 40mg daily resulted in significantly greater reduction of LDL-c compared to placebo. The 34% (-60% to +11%) reduction of risk for a major CVD event compared to placebo, although not statistically significant due to early termination of the trial, is in line with the Cholesterol Treatment Trialists' Collaboration meta-analysis of the effect of statins in other populations. Statin therapy was safe in patients with RA. Arthritis Research UK (Grants 16514 and 19704) and British Heart Foundation (Grant SP/06/001) Disclosure of Interest: None declared